Surgical resection of Haglund deformity by lateral approach: our institutional experience on 29 heels - Mir, Naseer A.; Ali, Nadeem; Khan, Kafeel; Dar, Tahir A.; Khandy, Rouf I.; Dhar, Shabir A. (International Journal of Research in Orthopaedics, 2018)
Background: Haglund deformity is a common cause of posterior heel pain and consists of a constellation of soft tissue and osseous abnormalities. The treatment starts with conservative approach and ends with surgical treatment in case conservative treatment fails and the symptoms are bothersome. Different surgical procedures and approaches have been used for this deformity. But in the literature, the results have been inconsistent. In this study we evaluated the clinical and functional outcome of osteotomy of the calcaneal tuberosity with debridement of the retrocalcaneal bursa and the Achilles tendon using a lateral approach at our institute. Methods: A total of 29 feet in 25 patients that underwent surgical procedure from August 2013 to March 2017 at our institute were included in this study. The clinical and functional outcome was evaluated using AOFAS ankle-hind foot scale. Results: The mean AOFAS ankle-hind foot score had improved by 32 points from the pre-operative mean score, with a mean score of 86 at the final follow up of one year. Five out of 29 operated feet had superficial surgical site infection in the postoperative period that responded to antibiotic therapy and regular antiseptic dressings. One patient had local betadine allergy. Conclusions: We conclude lateral approach to debridement and calcaneal tuberosity resection is an effective method with good clinical and functional outcome in patients with refractory Haglund deformity.